Language mask in modern social communication: media sphere - Шулінова, Лариса Василівна (Київський національний університет імені Тараса Шевченка, 2024)
Modern media communication as a component of society requires systematic research (especially the linguistic one) of the self-realization's possibilities of the person because the combination of the verbal and non-verbal components is the basis of media texts of various types and genres. The concepts of "personality type", "mask", "social mask", "media mask", "language mask" are considered within using of different criteria for their interpretation, where the language component is mostly optional and unrepresentative. The article focuses on the actualization of the language level for a more detailed scientific analysis in concepts, terms and approaches to investigation that are correlated with the requirements of nowadays. The actual definition of a mask in media communication is formulated. It is a social perception of person, that is modeled by an individual using verbal and non-verbal means in accordance with own intentions and / or requests of society or its individual groups. An own approach to the classification of language masks in the media is proposed according to verbal (systematically used language units of different levels to implement the goals and tasks of communication) and non-verbal (personality types from the point of view of psychology, language, style, genre functions) criteria. The conducted research gave grounds to distinguish the following language masks in the media: Intellectual, Informant, Advisor, Expert, Showman / Showwoman, Simpleton, Rebel, Provocateur, Caregiver, Sympathizer. The main language means for each of the masks are outlined, and for illustration, individual persons who carry these masks are named. It is emphasized that the proposed classification is an open system that should be considered as a starting model, that is characterized by variability (addition, deletion, modification), due to the development of social communication and information technologies, the needs of society, its individual groups and personalities. The prospects for further research are also outlined: more detailed analysis of the stated language markers, their expressive and influential potential, evolution of both individual language masks in the media and the personalities who use them, and clarification of the specifics of the different masks' coexistence in the communication of one person.

Сучасна медійна комунікація як складник суспільної потребує системних досліджень можливостей самореалізації особистості, а особливо мовної, адже саме поєднання вербального і невербального складника є основою медійних текстів різних типів і жанрів. Поняття "тип особистості", "маска", "соціальна маска", "медійна маска", "мовна маска" розглядають, застосовуючи різні критерії їх інтерпретації, де мовний складник здебільшого виявляється факультативним і нерепрезентативним. У статті зроблено акцент на актуалізації саме мовного рівня для більш детального наукового осмислення в поняттях, термінах та підходах до аналізу, що відповідають вимогам сьогодення. Сформульовано власне визначення маски в медійній комунікації – це змодельоване особистістю за допомогою вербальних і невербальних засобів сприйняття її соціумом відповідно до власних намірів і / чи запитів суспільства або окремих його груп. Запропоновано власний підхід до класифікації мовних масок у медіа за вербальними (системно вживані мовні одиниці різних рівнів для реалізації мети та завдань спілкування) і невербальними (типи особистостей із погляду психології, функції мовні, стильові, жанрові) критеріями. Проведене дослідження дало підстави виокремлювати такі мовні маски в медіа: Інтелектуал / Інтелектуалка, Інформатор / Інформаторка, Порадник / Порадниця, Експерт / Експертка, Шоумен / Шоувумен, Простак / Простачка, Бунтар / Бунтарка, Провокатор / Провокаторка, Піклувальник / Піклувальниця, Співчутливець / Співчутливиця. Окреслено основні мовні засоби для кожної з масок, задля ілюстрації названо окремих осіб-носіїв цих масок. Акцентовано на тому, що запропонована класифікація – відкрита система, яку варто розглядати як вихідну модель, якій властива змінність (поповнення, вилучення, видозміну, варіативність), зумовлена розвитком суспільної комунікації та інформаційних технологій, потребами суспільства, окремих його груп та персоналій. Перспективами подальших досліджень визначено більш детальний аналіз заявлених мовних засобів-маркерів, їх виражальний та впливовий потенціал, еволюція і щодо окремих мовних масок у медіа, і щодо особистостей, які ними послуговуються, та зʼясування специфіки співіснування різних масок у комунікації однієї особистості.
Мовна маска в сучасній суспільній комунікації: медійна сфера
Keywords: language mask; personality types; media communication; verbal means; мовна маска; типи особистостей; медійна комунікація; вербальні засоби